Findings and lessons from establishing Zika virus surveillance in southern Viet Nam, 2016 - Phan, Trong Lan; Luong, Chan Quang; Do, Thi Hong Hien; Chiu, Cindy H; Cao, Minh Thang; Nguyen, Thi Thanh Thao; Diep, Thanh Hai; Huynh, Phuong Thao; Nguyen, Tri Dung; Le, Hong Nga; Otsu, Satoko; Tran, Dac Phu; et al. (Western Pacific Surveillance and Response, 2019)
Objective: To document the evolution and optimization of the Zika virus (ZIKV) disease surveillance system in southern Viet Nam in 2016 and to describe the characteristics of the identified ZIKV-positive cases. Methods: We established a sentinel surveillance system to monitor ZIKV transmission in eight sites in eight provinces and expanded the system to 71 sites in 20 provinces in southern Viet Nam in 2016. Blood and urine samples from patients who met the case definition at the sentinel sites were tested for ZIKV using real-time reverse transcription polymerase chain reaction at the Pasteur Institute in Ho Chi Minh City (PI-HCMC). We conducted descriptive analysis and mapped the ZIKV-positive cases. Results: In 2016, 2190 specimens from 20 provinces in southern Viet Nam were tested for ZIKV at PI-HCMC; 626 (28.6%), 484 (22.1%), 35 (1.6%) and 1045 (47.7%) tests were conducted in the first, second, third and fourth quarters of the year, respectively. Of these tested specimens, 214 (9.8%) were ZIKV positive with 212 (99.1%) identified in the fourth quarter. In the fourth quarter, the highest positivity rate was those in age groups 30–39 years (30.0%) and 40–59 years (31.6%). Of the 214 ZIKV-positive patients, 210 (98.1%) presented with rash, 194 (90.7%) with fever, 149 (69.6%) with muscle pain, 123 (57.5%) with joint pain and 66 (30.8%) with conjunctivitis. Discussion: The surveillance system for ZIKV disease underwent several phases of optimization in 2016, guided by the most up-to-date local data. Here we demonstrate an adaptable surveillance system that detected ZIKV-positive cases in southern Viet Nam.